ONLINE JOURNALIST IDEALISM IN BANDUNG RAYA WITHIN HOAX VORTEX (Profetik: Jurnal Komunikasi, 2020)
Mass communication messages can be produced individually using internet facilities that can be accessed using various gadgets today. Everyone can be to send of any communication message to the public, including hoax message. The hoax is information or messages that are not supported by facts and data, so that is lie and cannot be justified. Hoax are made to confuse the atmosphere, attack and bring down others To day hoax can be  compete with communication message produced by any mass media, and any where including journalists in the Bandung Raya. This study aims to examine the idealism of online media journalists in the Bandung Raya area in the hoax vortex, so it takes of data in the form of opinions from online media journalists in Bandung Raya. Therefore, the appropriate research method in this research is descriptive method. Descriptive method seeks to describe the phenomenon or object of research in accordance with what is in the field. Therefore, the most appropriate approach to constructing opinions and experiences experienced by researchers and informants is a qualitative approach. The guiding theories in this research are social action theory, phenomenology and symbolic interaction theory which are also supported by concepts relevant to this research. Through interviews to journalists, the research results show that hoaxes for online media journalists in the Greater Bandung area can provide both positive and negative aspects to journalists' idealism.